Global Distribution of Marginal Accessory Tubercles of the Maxillary Premolars - Donovan M. Adams; Victoria M. Swenson; G. Richard Scott (Dental Anthropology Association, 2019)
The present study assesses the global distribution of marginal accessory tubercles of the maxillary premolars. This trait, despite constituting one of the variables standardized by Turner and colleagues (1991), has received little attention in morphological studies. Frequencies were calculated from data sheets collected by Christy G. Turner II for mesial, distal, and mesial + distal grades. Different geographic patterns were identified for both types of expression on the upper premolars. The patterned geographic distribution of these traits indicates their utility in biodistance investigations. In addition, the distinction between mesial and distal accessory tubercles specified by Scott and Irish (2017) is recommended, as these two traits exhibit different geographic patterns.